Triple crown leadership building excellent, ethical, and enduring organizations - Vanourek, Bob (McGraw-Hill, 2012)
Providing compelling leadership lessons from an array of enterprises; including Zappos; Google; eBay; Infosys; Xerox; Spotify; Mayo Clinic; KIPP; Ashoka; and more; this compelling book shows you how to achieve high performance; integrity; and sustainability. --
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Leadership -- Case studies; Business ethics; Social responsibility of business; Leadership; Études de cas; Morale des affaires; Entreprises; Responsabilité sociale; Management; Business & Economics; Management Styles & Communication; Case studies